2022
DOI: 10.3390/en15124203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Separator Thickness on Temperature Distribution in Single Cell of Polymer Electrolyte Fuel Cell Operated at Higher Temperature of 90 °C and 100 °C

Abstract: The New Energy and Industry Technology Development Organization (NEDO) road map (Japan, 2017) has proposed that a polymer electrolyte fuel cell (PEFC) system, which operates at a temperature of 90 °C and 100 °C, be applied for stationary and mobility usage, respectively. This study suggests using a thin polymer electrolyte membrane (PEM) and a thin gas diffusion layer (GDL), at the same time, to achieve better power-generation performance, at a higher temperature than usual. The focus of this paper is to clari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…From this report, the trapezoidal structure of cross-sectional area of the flow channel was the best shape to obtain the highest power generation performance. It also revealed that the pressure drop and the outlet power of the optimal model were larger by 1.7% and However, only a few papers [16] [18] investigated the temperature distribution near the interface between PEM and catalyst layer at the cathode, which is defined as a reaction surface in this study, excluding other studies by the authors [19]- [24]. The authors' studies [19]- [24] investigates the effect of PEM's thickness, GDL's thickness and separator's thickness on the distribution of the temperature at the reaction surface (T surf ), in a single cell of PEFC at a higher temperature such as 363 K and 373 K by 1D heat transfer model using the experimental temperature distribution data obtained by means of a thermograph.…”
Section: Introductionmentioning
confidence: 93%
“…From this report, the trapezoidal structure of cross-sectional area of the flow channel was the best shape to obtain the highest power generation performance. It also revealed that the pressure drop and the outlet power of the optimal model were larger by 1.7% and However, only a few papers [16] [18] investigated the temperature distribution near the interface between PEM and catalyst layer at the cathode, which is defined as a reaction surface in this study, excluding other studies by the authors [19]- [24]. The authors' studies [19]- [24] investigates the effect of PEM's thickness, GDL's thickness and separator's thickness on the distribution of the temperature at the reaction surface (T surf ), in a single cell of PEFC at a higher temperature such as 363 K and 373 K by 1D heat transfer model using the experimental temperature distribution data obtained by means of a thermograph.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, Japan's "FCV HDV Fuel Cell Technology Development Roadmap" announced the 2040 fuel cell development plan for heavy-duty vehicles, which will gradually raise the operating temperature to intermediate temperature [1,2]. Running fuel cells at intermediate temperatures can improve Oxygen reduction reaction (ORR) efficiency [3], increase the resistance of Pt-based electrocatalysts to CO poisoning, and simplify the water management of the cell and thermal management, among many other benefits [4,5].…”
Section: Introductionmentioning
confidence: 99%